Evaluation of the Implementation of Ecotourism-Based Tourism Policies in Indonesia: Challenges and Opportunities - Idrus, Sitti Hairani; Golok Jaya, Laode Muhammad; Yusuf, Muhammad; Rijal, Muh. (Universitas Syiah Kuala, 2024)
This article evaluates the implementation of ecotourism-based tourism policies in Indonesia, which is an effort to promote sustainable tourism while conserving natural and cultural resources. This research uses a qualitative approach with literature analysis and case studies to identify the challenges and opportunities faced. The results show that despite the government's commitment to promoting ecotourism, various obstacles such as inadequate infrastructure, lack of understanding of local communities, and negative environmental impacts are still significant challenges. However, the opportunity to develop ecotourism in Indonesia remains great, especially through increased community participation, sustainability promotion, and collaboration between the public and private sectors. These findings are expected to provide recommendations for policymakers in formulating more effective strategies to advance ecotourism-based tourism in Indonesia.